Management and characteristics of odontogenic facial infections in hospitalized pediatric patients. Retrospective study - Sánchez Huamán, Flora Martina (2023)
Objective: To describe the characteristics and management of odontogenic facial infections in pedia-tric patients hospitalized in a reference hospital in Cusco, Peru. Material and Methods: This descripti-ve, cross-sectional and retrospective study included a total of 90 medical records of children under 15 years of age who were hospitalized and treated for odontogenic infections at the Adolfo Guevara Ve-lasco National Hospital, Cusco-Peru during the years 2011-2016. Results: Odontogenic facial infections in male children (60%) aged between 1 and 4 years (52.22%) occurred more frequently. The infections occurred mainly in posterior teeth (76.67%), and at the upper region of the face (63.33%). The average length of stay in hospital was 4.58 ± 2.27 days. Clindamycin was the more used antibiotic therapy for the treatment of infections (57.78%); and the pulp chamber opening, and tooth drainage (56.67%) were the most performed dental treatments during hospitalization. Conclusion: Odontogenic facial infec-tions were more frequently in male children under 4 years of age. The infections occurred mainly in posterior teeth and at the upper region of the face. Pulp chamber opening and tooth drainage were the most frequent treatments; and Clindamycin was the antibiotic therapy most used.